A study on hybrid active noise control system combined with remote microphone technique. (30th March 2023) - Zheng, Xu; Jia, Zibin; Wan, Bo; Zeng, Minfang; Qiu, Yi
Highlights: A multichannel simplified hybrid ANC system combined the Remote Microphone Technique (RMT) method was proposed. The proposed system can provide a solution for a better arrangement of error microphones in the practical situation. The system can further compress the peak noise components that cannot be controlled by the traditional feedforward ANC. Abstract: This paper proposed a hybrid active noise control (HANC) system combined with virtual sensing technique. The Remote Microphone Technique (RMT) method was established in the time domain, and the optimal array of observation sensors of RMT method was determined by Genetic Algorithm (GA). Then with the pre-defined observation filter, a multichannel simplified HANC system combined RMT (msHANC-RMT) method was proposed. The off-line simulations were executed with the data collected from the tests in a semi-anechoic chamber. The results showed that the msHANC-RMT system had the similar control capability compared to the msHANC system in all noise conditions, which can further compress the peak frequency components in the noise spectrum that cannot be detected and controlled by the traditional feedforward ANC (FFANC) system. However, the msHANC-RMT system was more sensitive to delays compared to the FFANC system, once the additional delays exceeded several milliseconds, the feedback structure in msHANC-RMT system lost most of the control capacity.